Philosophical Practice as Spiritual Exercises towards Truth, Wisdom, and Virtue - Ding, Xiaojun (Religions, 2022)
The concept of spirituality has a long philosophical history. Based on detailed studies of a history of spiritual exercises from Socrates, the Stoics, Epicureanism, to early Christianity, the former catholic priest Pierre Hadot conceives philosophical practice as spiritual exercises in learning how to live a philosophical life. Following this idea, a number of philosophers such as Gerd B. Achenbach started the contemporary movement of philosophical practice in the 1980s, which aimed to apply philosophical theories and methods to discussions about issues people constantly encounter in life, mainly in the forms of philosophical counseling and philosophical therapy. In this paper, after showing that philosophical practice has already become a new frontier in philosophical research, we further argue that philosophical practice as spiritual exercises is an exercise of reason and logos, while certain kinds of religious exercises such as Zen arts can also constitute an important part of philosophical practice. We conclude that in light of the distinct plurality of the methods and modes of philosophical practice and the spiritual exercises involved, philosophical practice can be considered a meaningful and applicable approach to pursuing truth, wisdom, and virtue, which is of great didactic and ethical significance in the post-COVID-19 era.